Glycan Modulation of Insulin‐like Growth Factor‐1 Receptor. Issue 49 (9th November 2022) - Boothello, Rio S.; Sankaranarayanan, Nehru Viji; Sistla, Jyothi C.; Nagarajan, Balaji; Sharon, Chetna; Chittum, John E.; Niyaz, Rabiya Y.; Roy, Swarnali; Nandi, Aditi; O'Hara, Connor P.; Gangji, Rahaman Navaz; Afosah, Daniel K.; et al.
Abstract: The insulin‐like growth factor‐1 receptor (IGF‐1R) is a receptor tyrosine kinase (RTK) that plays critical roles in cancer. Microarray, computational, thermodynamic, and cellular imaging studies reveal that activation of IGF‐1R by its cognate ligand IGF1 is inhibited by shorter, soluble heparan sulfate (HS) sequences (e.g., HS06), whereas longer polymeric chains do not inhibit the RTK, a phenomenon directly opposed to the traditional relationship known for GAG‐protein systems. The inhibition arises from smaller oligosaccharides binding in a unique pocket in the IGF‐1R ectodomain, which competes with the natural cognate ligand IGF1. This work presents a highly interesting observation on preferential and competing inhibition of IGF‐1R by smaller sequences, whereas polysaccharides are devoid of this function. These insights will be of major value to glycobiologists and anti‐cancer drug discoverers. Abstract : The work provides a new insight into insulin‐like growth factor‐1 receptor (IGF‐1R), which is preferentially inhibited by smaller heparan sulfate chains, e.g., HS06, in contrast to longer polysaccharidic chains, e.g., HS36, which are devoid of the inhibition function.